Molecular Correlates of Socioeconomic Status and Clinical Outcomes Following Hematopoietic Cell Transplantation for Leukemia. Issue 4 (12th September 2019) - Knight, Jennifer M; Rizzo, J Douglas; Wang, Tao; He, Naya; Logan, Brent R; Spellman, Stephen R; Lee, Stephanie J; Verneris, Michael R; Arevalo, Jesusa M G; Cole, Steve W
Abstract: Background: Clinical outcomes among allogeneic hematopoietic cell transplant (HCT) recipients are negatively affected by low socioeconomic status (SES), yet the biological mechanisms accounting for this health disparity remain to be elucidated. Among unrelated donor HCT recipients with acute myelogenous leukemia, one recent pilot study linked low SES to increased expression of a stress-related gene expression profile known as the conserved transcriptional response to adversity (CTRA) in peripheral blood mononuclear cells, which involves up-regulation of pro-inflammatory genes and down-regulation of genes involved in type I interferon response and antibody synthesis. Methods: This study examined these relationships using additional measures in a larger archival sample of 261 adults who received an unrelated donor HCT for acute myelogenous leukemia to 1) identify cellular and molecular mechanisms involved in SES-related differences in pre-transplant leukocyte transcriptome profiles, and 2) evaluate pre-transplant CTRA biology associations with clinical outcomes through multivariable analysis controlling for demographic-, disease-, and transplant-related covariates. Results: Low SES individuals showed increases in classic monocyte activation and pro-inflammatory transcription control pathways as well as decreases in activation of nonclassic monocytes, all consistent with the CTRA biological pattern. Transplant recipients in the highest or lowest quartiles of the CTRA pro-inflammatory gene component had a more than 2-fold elevated hazard of relapse (hazard ratio [HR] = 2.47, 95% confidence interval [CI] = 1.44 to 4.24), P  = .001; HR = 2.52, 95% CI = 1.46 to 4.34, P  = .001) and more than 20% reduction in leukemia-free survival (HR = 1.57, 95% CI = 1.08 to 2.28, P  = .012; HR = 1.49, 95% CI = 1.04 to 2.15, P  = .03) compared with the middle quartiles. Conclusions: These findings identify SES- and CTRA-associated myeloid- and inflammation-related transcriptome signatures in recipient pre-transplant blood samples as a potential novel predictive biomarker of HCT-related clinical outcomes.